Linguistic Frontiers: Pioneering Breakthroughs in Computational Language Technology - Murali Krishna Pasupuleti (Cutting Edge Advances in Computational Linguistics, 2024)
Abstract: This chapter explores the cutting-edge advancements in computational language technology, delving into the transformative impact of recent innovations in the field. It covers the evolution from traditional rule-based and statistical methods to advanced neural network architectures, such as Recurrent Neural Networks (RNNs), Convolutional Neural Networks (CNNs), and Transformers. The chapter highlights key applications in natural language processing (NLP), including speech recognition, machine translation, and sentiment analysis, while addressing the ethical and societal implications of these technologies. Emphasis is placed on emerging research areas, such as multilingual NLP, low-resource language processing, and conversational AI. The chapter concludes by discussing future trends and challenges, including scalability, interpretability, and fairness in NLP systems, providing a comprehensive overview of the current state and future directions of computational linguistics. Keywords: Computational Linguistics,Natural Language Processing (NLP),Neural Networks,Deep Learning,Speech Recognition,Machine Translation,Sentiment Analysis,Multilingual NLP,Low-Resource Languages,Conversational AI,Ethical AI,Data Privacy,Algorithmic Bias and Future Trends in NLP. References: Bei, S. (2024). Integrative Analysis of Socio-linguistic Principles in Applied Language Teaching. Frontiers in Education Technology, 7(1), p58. https://doi.org/10.22158/fet.v7n1p58 Bender, E. M., & Langendoen, D. T. (2010). Computational Linguistics in Support of Linguistic Theory. Linguistic Issues in Language Technology, 3. https://doi.org/10.33011/lilt.v3i.1213 Chandlee, J., & Jardine, A. (2021). Computational universals in linguistic theory: Using recursive programs for phonological analysis. Language, 97(3), 485–519. https://doi.org/10.1353/lan.2021.0045 Frank, A., Zaenen, A., & Hinrichs, E. (2012). Treebanks: Linking Linguistic Theory to Computational Linguistics. Linguistic Issues in Language Technology, 7. https://doi.org/10.33011/lilt.v7i.1259 Oseki, Y. (2023). Chapter 15 Human language processing in comparative computational psycholinguistics. Cross-Linguistic Studies, 269–288. https://doi.org/10.1515/9783110778946-015 R’boul, H. (2024). English as a subtle technology of distraction in postcolonial contexts: undoing linguistic colonialism by linguistic coloniality. Current Issues in Language Planning, 1–20. https://doi.org/10.1080/14664208.2024.2355392 Steffensen, S. V., Fowler, C., & Trousdale, G. (2017). Language sciences: Half a century on the linguistic frontiers. Language Sciences, 59, A1–A4. https://doi.org/10.1016/j.langsci.2016.11.003